Purification and Properties of Cytoplasmic and Mitochondrial Malate Dehydrogenases of Physarum polycephalum - Teague, W. Martin (1973)
Two isoenzymes of malate dehydrogenase (MDH) were demonstrated in plasmodia of Physarum polycephalum by polyacrylamide-gel electrophoresis. The more “cathodal” form was uniquely associated with mitochondria (M-MDH) and the other form was found in the soluble cytoplasm (S-MDH). The isoenzymes were separated by acetone fractionation of soluble plasmodial homogenates acidified to pH 5.0. The M-MDH was purified 201-fold by cetylpyridinium chloride treatment, fractionation with ammonium sulfate, gradient elution from sulfoethyl cellulose at pH 6.0, and Sephadex G-100 chromatography. The S-MDH was purified 155-fold by ammonium sulfate fractionation, diethylaminoethyl cellulose chromatography, gradient elution from sulfoethyl cellulose at pH 5.5, and Sephadex G-100 chromatography. The optimal cis-oxalacetate concentrations were 0.35 mM for M-MDH and 0.25 mM for S-MDH, and the optimal pH for both isoenzymes was 7.6 for oxalacetate reduction. The optimal l-malate concentrations were 5 mM for S-MDH and 6 mM for M-MDH, and both isoenzymes exhibited an optimal pH of 10.0 for L-malate oxidation. The Michaelis constants of S-MDH and M-MDH served to discriminate between the isoenzymes. The S-MDH was more heat-stable than the M-MDH. High concentrations of oxalacetate and malate inhibited S-MDH more than M-MDH. The isoenzymes were further distinguished by their utilization of analogues of nicotinamide adenine dinucleotide. Many properties of the Physarum isoenzymes were similar to those of more complex organisms, especially vertebrates.